Ẓāhirah Ribu Waikāsān fī Qaryah Wūnukrūmū, Bantūl, Yūjyākārtā fī Ḍawʾ al-ʿAqīdah wa al-Syarīʿah al-Islāmiyyah - Syihab, Usman; Ridho, Hanif Muhammad; Sahabuddin, Sahabuddin (Al-Zahra : Journal for Islamic and Arabic Studies, 2024)
This research examines the Rebo Wekasan tradition carried out in Wonokromo Village, Pleret, Bantul, Yogyakarta from the perspective of Islamic Aqidah and Shariah. Rebo Wekasan is an annual ritual held on the last Wednesday of the month of Safar in the Hijri calendar. The aim of this research is to analyze the conformity of Rebo Wekasan practices with the principles of Islamic Aqidah and Shariah. The research method used was qualitative by collecting data through in-depth interviews with religious figures, government officials, ritual practitioners and Wonokromo residents, as well as through literature studies related to Aqidah and Shariah. The research reveals that although Rebo Wekasan is rooted in pre-Islamic traditions, the Wonokromo people have made various modifications to align it with Islamic teachings. This research concludes that Rebo Wekasan in Wonokromo reflects the dynamics of acculturation between Javanese and Islamic culture. The community seeks to maintain their cultural identity while adhering to the principles of Tauhid